Multi Body Approach to Dynamical System: The Case of Wind Turbine - Harun, Mohamad Bakhit Aiman (Universiti Teknologi PETRONAS, 2017)
This study focuses on the development and analysis of foundation of a wind turbine using multibody approaches as design method. By using multibody system, the model is divided into three main bodies which are the blade, tower, and the foundation. The connection between these bodies will describe the motions of the wind turbine when dynamical loads are applied to the blade. Modeling using fixed tower omitting the effect of the foundation due to the pitching and yawing motions. One objective is to simulate the wind turbine dynamical deformations thus see the effect on the foundation. For this project, MATLAB and Simulink is used to model and simulate the effect of the foundation by applied dynamic forces through the stream tubes of the blade after it was divided into several elements using Blade Element Momentum Theory. The effect on the foundation is then determined by performing parametric study based on the wind speed, surface area of pile, and different length of pile foundation.